Positive solutions for systems of nonlinear second‐order multipoint boundary value problems. (10th October 2013) - Henderson, Johnny; Luca, Rodica
Abstract We study the existence of positive solutions for systems of second‐order nonlinear ordinary differential equations, subject to multipoint boundary conditions. Copyright © 2013 John Wiley & Sons, Ltd.